2021
DOI: 10.1002/elps.202000301
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of electroosmotic flow markers in capillary zone electrophoresis

Abstract: UV‐absorbing neutral substances are commonly used as markers of mean electroosmotic flow in capillary electrophoresis for their zero electrophoretic mobility in an electric field. However, some of these markers can interact with background electrolyte components and migrate at a different velocity than the electroosmotic flow. Thus, we tested 11 markers primarily varying in their degree of methylation and type of central atom in combination with five background electrolyte cations differing in their ionic radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…For measurement of the EOF velocity and mobility, the selection of a suitable electroneutral marker is important. As shown in a recent article [97], some of the commonly used EOF markers may interact with the BGE constituents and may move with nonzero electrophoretic mobility. This may result in the biased EOF mobility of the markers and effective mobility of the analytes.…”
Section: Suppression Of Peptide Sorption and Control Of Eofmentioning
confidence: 99%
“…For measurement of the EOF velocity and mobility, the selection of a suitable electroneutral marker is important. As shown in a recent article [97], some of the commonly used EOF markers may interact with the BGE constituents and may move with nonzero electrophoretic mobility. This may result in the biased EOF mobility of the markers and effective mobility of the analytes.…”
Section: Suppression Of Peptide Sorption and Control Of Eofmentioning
confidence: 99%
“…For measurement of the EOF velocity and mobility, the selection of a suitable electroneutral marker is important. Martinkova et al [120] have shown that some of the commonly used EOF markers may interact with the BGE constituents and may move with nonzero electrophoretic mobility. This may result in the biased EOF mobility of the markers and effective mobility of the analytes.…”
Section: Suppression Of Peptide Adsorption and Regulation Of Eofmentioning
confidence: 99%
“…The EOF in capillary columns and microchannels is important for CE and electroosmotic pumping applications [7][8][9]. However, because of the difficulties of fabricating microchannels by FDM 3D printing, few works [10,11] were found in the literature studying EOF for the most common materials used as thermoplastic filaments.…”
mentioning
confidence: 99%